Form of Business Responsibility for Consumer Losses Caused by Misleading Promotions - Mulia Akbar Santoso; Muskibah Muskibah; Johni Najwan (Science and Environmental Journal for Postgraduate, 2023)
The purpose of this study is to analyze the form of accountability of business actors when there are losses experienced by consumers who consume products because they are interested in the promotion of these products. To analyze the objectives of this study, this research method uses normative juridical research methods, using a statutory approach obtained through literature and documents. Legal responsibility must have a basis; accountability has to do with violation of a regulation as well as an obligation that must be carried out based on agreements or legal provisions. Business actors who provide misleading information in marketing their products can be held responsible for losses suffered by consumers due to promotions.